From radiocarbon analysis to interpretation: A comment on "Phytolith Radiocarbon Dating in Archaeological and Paleoecological Research: A Case Study of Phytoliths from Modern Neotropical Plants and a Review of the Previous Dating Evidence", Journal of Archaeological Science (2015), doi: 10.1016/j.jas.2015.06.002." by Dolores R. Piperno. (July 2016) - Santos, Guaciara M.; Alexandre, Anne; Prior, Christine A.
Abstract: The paper "Phytolith Radiocarbon Dating in Archaeological and Paleoecological Research: A Case Study of Phytoliths from Modern Neotropical Plants and a Review of the Previous Dating Evidence" by Dolores R. Piperno presents radiocarbon analysis of phytoliths from modern Neotropical plants collected between 1964 and 2013. The analyses presented were intended to rebut the emerging hypothesis that invokes root-plant uptake, transport and reallocation of soil organic carbon into phytoliths that has been recently put forward as an explanation for the anomalous radiocarbon ( 14 C) ages (of hundreds to thousands of years old) reported for modern grass phytoliths in Santos et al. (2010a, 2012a, b). We believe that the results presented inPiperno (2015) lack methodological rigor, mostly due to the absence of any procedural blank assessment, and that the attempts to disprove the hypothesis of uptake of soil organic matter (SOM) by phytoliths in Santos et al. (2012a) are not supported by a careful analysis. Rather than supporting the position that 100% of the carbon in phytoliths is of photosynthetic origin, which allows the use of phytolith carbon (or phytC) as a dating tool, the analysis of 14 C in phytoliths from modern Neotropical plants presented in the study shows that the 14 C ages are strongly affected by other sources of carbon. In this comment, we carefully reassess the 14 C results in phytoliths from modern Neotropical plants presented inPiperno (2015) in the context of the 14 C bomb-pulse methodology, SOM ages and turnover rates, and offer an alternative interpretation of the experimental results. Graphical abstract: